ANALYSIS ON THE STUDENTS’ COMMON DIFFICULTIES IN TOEFL READING COMPREHENSION (A CASE STUDY ON THE SECOND SEMESTER OF ENGLISH STUDY PROGRAM AT ISLAMIC UNIVERSITY OF INDRAGIRI TEMBILAHAN) - Maizarah Maizarah (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
The problem in this study was the students’ common difficulties in TOEFL Reading Comprehension. This study only used one variable. The research method used in this study was a descriptive research. The purpose of this study was to know the students’ common difficulties in TOEFL Reading Comprehension on the second semester of English Study Program at Islamic University of Indragiri Tembilahan. The total of the sample used in this study were 23 students, the technique was used to take the sample is total sampling. In collecting the data, the researcher used a test. After the data has been collected, the result of test showed that the skills that are considered to be the most difficult ones in TOEFL reading, which is skill 3. This skill is identifying stated detail questions correctly. It is the highest percentage (84%) with the total of incorrect answer is 210 from 5 items. Then, it is followed by skill 5 (82%) with the total of incorrect answer is 82 from 2 items, which is finding pronoun reference. It is the second most difficult skill for the students. The third most difficult skill is skill 7. It is responding of transition question achieve 81% with the total of incorrect answers is 81 from 2 items. Next, skill 10 is considered to be the fourth most difficult skill in TOEFL reading comprehension. The questions are about the use of context to give meaning of difficult word which is counted 80 % from the total of incorrect answers is 120 from 3 items. Then, the fifth most difficult skill in TOEFL reading comprehension is skill 1, which is consisting the questions about answering main idea questions correctly, students made 78% of the total incorrect answers is 156 from 4 items.